The Development of VN Application-Based Learning Videos on Writing Skill of Descriptive Texts for Seventh Grade Students at SMPN 01 Tebo Regency - Salahuddin, Amar; Aprimadedi, Aprimadedi; Sahlan, Sahlan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to develop an instructional medium using the VN application for teaching descriptive text writing. The researcher chose the VN application because it is practical and easy to use for creating learning videos designed to actively engage students’ visual and auditory senses, there by optimizing the absorption of the material. This research employed a research and development (R&D) method with a 4D model, consisting of the stages of define, design, develop, and disseminate. The study was conducted at SMPN 01 Tebo Regency in the 2024/2025 academic year with a research subject of 29 seventh-grade students. Data collection techniques included student response questionnaires, teacher responses, and validation sheets from media experts, material experts, and language experts. The results showed that the researcher success fully produced a learning video as a medium for teaching descriptive text writing. The media was deemed valid based on expert validations: media expert validation scored 95% (categorized as “highly valid”), material expert validation scored 85% (“valid”), and language expert validation also scored 85% (“highly valid”). This indicates that the learning video is suitable for use by teachers and students. Furthermore, practicality assessments revealed a score of 96.3% from teachers and 97.6% from students, both categorized as “highly valid.” Thus, it can be concluded that the learning video developed by the researcher is feasible for use, as it meets the criteria of being valid, practical, and effective.